2009
DOI: 10.1073/pnas.0906514106
|View full text |Cite
|
Sign up to set email alerts
|

Peptides modulating conformational changes in secreted chaperones: From in silico design to preclinical proof of concept

Abstract: Blocking conformational changes in biologically active proteins holds therapeutic promise. Inspired by the susceptibility of viral entry to inhibition by synthetic peptides that block the formation of helixhelix interactions in viral envelope proteins, we developed a computational approach for predicting interacting helices. Using this approach, which combines correlated mutations analysis and Fourier transform, we designed peptides that target gp96 and clusterin, 2 secreted chaperones known to shift between i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…A recent study reported that a peptide sequence targeting part of the charged linker region of gp96 was able to inhibit endotoxic shock when administered in vivo (36). It is noteworthy that CBD-targeted peptide is able to significantly inhibit gp96-integrin interaction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that a peptide sequence targeting part of the charged linker region of gp96 was able to inhibit endotoxic shock when administered in vivo (36). It is noteworthy that CBD-targeted peptide is able to significantly inhibit gp96-integrin interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, gp96 appears to be an attractive drug target for inflammation, sepsis, and autoimmune disease. In a recent study utilizing in silico methods, a peptide inhibitor of gp96 was designed by targeting the N-terminal helix-loop-helix sequence, and the authors demonstrated that this peptide could effectively inhibit LPS responses both in vitro and in vivo (24). The proposed mechanism of action was that this peptide mimics the sequence of the helix, therefore disrupting the helix-helix interaction and the chaperoning function of gp96.…”
Section: Heat-shock Protein 90 (Hsp90)mentioning
confidence: 99%
“…As proposed by the Kliger et al (24) study, the design of PIER1 peptide is based on a potential helix-helix interaction between PIER1 and the target sequence in the HSP that requires a conformation-dependent interaction. To examine this possibility, we designed another peptide, PIER2, by substituting the middle two residues in the helix of PIER1, Val and Arg, with two Pro residues.…”
Section: Pier Peptide Inhibits Nfb Response To Lps But Not Tomentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility is currently being exploited in clinical trials [81] by the successful paradigm of OGX-011, a 2'-methoxyethyl-modified phosphorothioate antisense oligonucleotide that is complementary to CLU mRNA; work in progress aims to finalize plans for two phase III clinical studies. Additional translational applications in relation to CLU biology may include peptides that bind and inhibit CLU in vivo [82] or molecular imaging of tumors by using CLU-binding fluorescent peptides [83]. …”
Section: Concluding Remarks: Future Perspectivesmentioning
confidence: 99%